A Comfortable Learning Climate as an Effort to Improve instruction quality and students’ Learning Outcomes: Case Study in Elementary School Banda Aceh - Susianti, Susianti; Rahmattullah, Rahmattullah; Fitriati, Fitriati; Sari, Siti Mayang (Faculty of Social Science, Universitas Negeri Padang, 2026)
A comfortable learning climate plays a crucial role in improving the quality of instruction and students’ learning outcomes in elementary schools. This study aims to analyze how a supportive, safe, and engaging learning environment contributes to instructional quality and enhances students’ academic achievement. Employing a qualitative case study approach, the research was conducted at an elementary school in Banda Aceh. Data were collected through classroom observations, in-depth interviews with teachers and school principals, and analysis of instructional documents. The findings indicate that a comfortable learning climate characterized by positive teacher–student interactions, inclusive classroom management, adequate learning facilities, and emotional support significantly improves teachers’ instructional practices and students’ learning motivation. Furthermore, students demonstrated higher participation, better understanding of learning materials, and improved learning outcomes. The study concludes that creating a comfortable learning climate is a strategic effort to enhance instructional quality and optimize students’ learning outcomes in elementary education. These findings provide practical implications for teachers and school leaders in designing learning environments that support effective and meaningful learning.